If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 13 = -9x + -20 Reorder the terms: 13 + 2x = -9x + -20 Reorder the terms: 13 + 2x = -20 + -9x Solving 13 + 2x = -20 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 13 + 2x + 9x = -20 + -9x + 9x Combine like terms: 2x + 9x = 11x 13 + 11x = -20 + -9x + 9x Combine like terms: -9x + 9x = 0 13 + 11x = -20 + 0 13 + 11x = -20 Add '-13' to each side of the equation. 13 + -13 + 11x = -20 + -13 Combine like terms: 13 + -13 = 0 0 + 11x = -20 + -13 11x = -20 + -13 Combine like terms: -20 + -13 = -33 11x = -33 Divide each side by '11'. x = -3 Simplifying x = -3
| 9(x+13)=9x+117 | | 15+7x=8(x-2) | | 5x-3(y)=22 | | -2q+4q=0 | | -1/7x=-8 | | 5(2)-3(-2-2)=22 | | 124/12 | | 10+2x=8(x-2) | | 0.4(x-3)=0.6x+1.8 | | 4(x+2)=4(x+15) | | 7/2x=40 | | 8y-18=3(y+3) | | x=17-15.5x | | 6-3x=10x-3 | | 1/10:1/8:1/6 | | x+2.5x=28 | | 2+4ln(x)=7 | | lnx-lny=c | | 6(x+3)-8x=6 | | 2(x+2)=(x+1)3 | | 2p-5=11 | | R=p/l2 | | 3x+10=2x+23 | | (22c^11)(x^17)(y^14)/(2c^8)(c^15)(y^10) | | 7d+6=42 | | 4t-6=2t+18 | | (5u+3)(5+u)=0 | | -3/9P=-2 | | 8-12(sin^2)x=4(cos^2)x | | -(w+5)+2w-11=-27 | | 4z+2z=5z-3 | | d(t)=360-60t |